Binayan, Narciso: "Ideario de Mayo". Buenos Aires, Editorial Kapelusz, 565 págs. - Martin, Elvira Luisa (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Historia., 1961)

(untitled)
Fil: Martin, Elvira Luisa.